Effect of percutaneous nephrolithotripsy under guidance of B-ultrasound for the treatment of complex renal calculi - Zhang, Jiajie; Xiao, Ning; Huang, Kun; Xu, Fangming; Pan, Gaoyu; Bo, Ge (Journal of the Pakistan Medical Association, 2022)
The purpose of this study was to investigate the effect of percutaneous nephrolithotripsy guided by B-ultrasound in the treatment of complex renal calculi. A total of 82 patients with complex renal calculi were selected, who underwent percutaneous nephrolithotripsy guided by B-ultrasound. The average operation time was 101.52 ±8.35 minutes, the average intraoperative bleeding volume was 132.86 ±7.22 ml, the average hospital stay was 10.47 (±1.68) days, the primary calculi clearance rate was 85.37% (70 cases), and the secondary calculi clearance rate was 95.12% (78 cases). Postoperative complications occurred in 18 (21.95%) cases, including fever in 13 (15.85%), residual stone in 4 (4.88%), and delayed bleeding in 1 (1.22%) case. The findings show that percutaneous nephrolithotripsy guided by B-ultrasound is safe and effective in the treatment of complex renal calculi and is suitable for popularisation and application in primary hospitals. Key words: B-ultrasound; complex renal calculi; percutaneous nephrolithotomy